2018
DOI: 10.1002/prca.201800046
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Class Prediction Model to Discriminate Pancreatic Ductal Adenocarcinoma from Pancreatic Neuroendocrine Tumor by MALDI Mass Spectrometry Imaging

Abstract: Purpose To define proteomic differences between pancreatic ductal adenocarcinoma (pDAC) and pancreatic neuroendocrine tumor (pNET) by matrix‐assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI). Experimental design Ninety‐three pDAC and 126 pNET individual tissues are assembled in tissue microarrays and analyzed by MALDI MSI. The cohort is separated in a training (52 pDAC and 83 pNET) and validation set (41 pDAC and 43 pNET). Subsequently, a linear discriminant analysis (LDA) model based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The classification of MSI data has been mainly performed using LDA and SVM [14][15][16][17][18][19][20]. An RF classification algorithm has previously been applied to classify MSI data but not on a large clinically relevant sample cohort [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The classification of MSI data has been mainly performed using LDA and SVM [14][15][16][17][18][19][20]. An RF classification algorithm has previously been applied to classify MSI data but not on a large clinically relevant sample cohort [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of this biomarker is associated with the diagnosis of malignant prostate cancer [ 35 ]. Extensive proteomic research with MALDI MSI was performed by Casadonte et al [ 36 ] on pancreatic ductal adenocarcinoma and pancreatic neuroendocrine tumor tissues, leading to the development of a class prediction model to differentiate between both entities with high accuracy, essential for the appropriate treatment modality. MALDI MSI proteomic analyses has also proven their relevance in triple-negative breast cancer in the search for putative markers for recurrence-free survival: Phillips et al [ 37 ] identified nine proteins, not previously associated with breast cancer, that were significantly associated with worse recurrence-free survival when these proteins were highly expressed.…”
Section: Maldi Mass Spectrometry Imaging In Cancer Researchmentioning
confidence: 99%
“…Among those, mass spectrometry imaging (MSI) has prompted interest among pathologists, as it combines the detection of multiple proteins or peptides with information about their topographical localization within tissue sections. The method was previously used to classify different cancer subtypes 12 - 14 . However, this technique has rarely been applied to study renal tumors and data on the differential expression patterns in cRCC and rO is lacking so far 15 - 17 .…”
Section: Introductionmentioning
confidence: 99%